2015
DOI: 10.4267/pollution-atmospherique.4894
|View full text |Cite
|
Sign up to set email alerts
|

Estimating atmospheric deposition of heavy metals in Germany using LOTOS-EUROS model calculations and data from biomonitoring programmes

Abstract: Objectives. Atmospheric deposition of heavy metals (HM) can be determined by use of numeric models, technical devices or measurements on biomonitors such as mosses, leaves or needles. As part of the research and development project "Impacts of Heavy Metal Emission on Air Quality and Ecosystems across Germany -Sources, Transport, Deposition and potential Hazards" , commissioned by the Federal Environmental Agency of Germany, the numeric model LOTOS-EUROS was used to calculate data on HM deposition at a spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This difference of land uses should evidently induce a discrepancy between the modeled deposition in the meshes and what is measured in the cemeteries. In Germany, Nickel et al [37] also demonstrated the importance of the deposition model taken into consideration in the correlations and showed a better correlation between modeled atmospheric deposition and Cd concentrations in mosses with deposit data modeled by LOTOS-EUROS which considers the land use, unlike deposits modeled by EMEP.…”
Section: Discussionmentioning
confidence: 99%
“…This difference of land uses should evidently induce a discrepancy between the modeled deposition in the meshes and what is measured in the cemeteries. In Germany, Nickel et al [37] also demonstrated the importance of the deposition model taken into consideration in the correlations and showed a better correlation between modeled atmospheric deposition and Cd concentrations in mosses with deposit data modeled by LOTOS-EUROS which considers the land use, unlike deposits modeled by EMEP.…”
Section: Discussionmentioning
confidence: 99%